Bimetallic ZIF-derived cobalt nanoparticles anchored on N- and S-codoped porous carbon nanofibers as cathode catalyst for Li-O2 batteries. (20th June 2022) - Guo, Shiquan; Sun, Yaxin; Wang, Jiaona; Peng, Lichong; Li, Huiyu; Li, Congju
Highlights: 1D porous N- and S-codoped carbon nanofibers anchored Co nanoparticles are developed. Co@N/S-CNF electrode exhibits improved electrochemical performance. Both Li2 O2 and LiOH discharge products can be effectively decomposed. The enhanced performances depend on the 1D porous morphology and N/S doping effect. Abstract: Metal-organic frameworks (MOFs) have shown great application potential for improving Lithium-oxygen (Li-O2 ) batteries performance with high O2 affinity and accessible active centers. Herein, a novel type of cobalt nanoparticles embedded in porous nitrogen (N)- and sulfur (S)-codoped carbon nanofiber (Co@N/S-CNF) structure is developed by employing electrospinning technology and bimetallic zeolitic imidazole framework (ZIF-8/ZIF-67, a kind of MOF) precursor with the following annealing and hydrothermal treatment route. When utilized as cathode catalysts for Li-O2 batteries, the Co@N/S-CNF sample exhibits higher discharge capacity (9290.7 mAh g −1 at 50 mA g −1 ) and better cycling stability (42 cycles at 100 mA g −1 under a curtailing capacity of 500 mAh g −1 ) compared to Co@N-CNF electrode. The enhanced performance can be attributed to the 1D porous morphology and N/S doping effect, which can effectively improve mass transport, increase exposed active sites, and induce structural defect, thereby accelerating the formation and decomposition progress of discharge products. This simple synthetic strategy may provide a new insight for designing and developing MOFs-based multifunctional catalysts in the field of energy and electrocatalysis. Graphical abstract: Bimetallic MOF precursors derived 1D porous N- and S-codoped carbon nanofibers wrapped Co nanoparticles (Co@N/S-CNF) are developed by employing electrospinning technology, in-situ growth strategy, solvothermal and annealing treatment. Benefit from the improved increased active sites and structural defect induced by N/S doping effect, the assembled Li-O2 batteries exhibit improved electrocatalytic performance. Image, graphical abstract